Oral Health Epidemiological Investigation in an Urban Homeless Population - Roberta Lione; Massimo Ralli; Francesca Chiara De Razza; Giuseppe D'Amato; Andrea Arcangeli; Luigi Carbone; Paola Cozza (MDPI AG, 2024)
The purpose of this clinical epidemiological investigation was to examine the oral health conditions of homeless people in the city of Rome, Italy. A total of 157 homeless subjects were subjected to a first dental visit, during which anamnestic information was recorded in a digital medical record. A diagnosis of dental disorders was performed by assessing oral hygiene conditions, periodontal health, the presence of caries and/or root residues, and the presence of partial and/or total edentulousness. Caries and missing teeth were evaluated by the DMFT index. The first major criticality was represented by poor or absent oral hygiene. The examined sample showed a major percentage of high DMFT (63.0%); the most common clinical condition was the presence of numerous root residues. Regarding periodontal health, 73.2% of patients had gingivitis, 21.6% periodontitis, while 11 patients had periodontal pathologies with tooth mobility (7%). Finally, 8.9% of patients had one or two missing elements, 22.9% had partial edentulousness, and 8.9% of the sample had total edentulism. This analysis provides an important basis for strengthening health promotion and the importance of accessible and effective care for this population. It will therefore be necessary to continue to adopt a patient-centered approach geared towards addressing the demands that this population faces in maintaining their oral health.